Graphic medicine: utilising comic for mental health awareness / Atikah Najeeha Azhari - Azhari, Atikah Najeeha (Faculty of Art and Design, 2020)
I have stumbled upon 'graphic medicine', a term for the practice of explaining medical issues through arts during my study and has been deeply intrigued by the subject ever since.